1998
DOI: 10.1021/ja973116c
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Study of Cyclodecane and Substituted Cyclodecanes by Dynamic NMR Spectroscopy and Computational Methods

Abstract: Low-temperature 13C NMR spectra of cyclodecane (1) showed the presence of a minor conformation, assigned to the twist-boat-chair-chair (TBCC), in addition to the expected boat-chair-boat (BCB). If only the TBCC and BCB conformations were assumed to be appreciably populated, then a free-energy difference between the two conformations of 0.73 ± 0.3 kcal/mol could be obtained from the five area measurements over a temperature range of −148.6 to −131.0 °C, with populations of 5.2 and 94.8% for the TBCC and BCB con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…13 C NMR studies have shown that at a low-temperature BCB is the principal conformer [35]. At room temperature, cyclodecane exists as a mixture of a rather large number of conformations.…”
Section: Cyclodecanementioning
confidence: 99%
“…13 C NMR studies have shown that at a low-temperature BCB is the principal conformer [35]. At room temperature, cyclodecane exists as a mixture of a rather large number of conformations.…”
Section: Cyclodecanementioning
confidence: 99%
“…Electron diffraction experiments have been of great aid to provide population data for cycloalkanes for gas phase samples, as reported for cycloheptane (Dillen & Geise, 1979), cyclooctane (Dorofeeva et al, 1985), cyclodecane (Hilderbrandt, Wieser & Montgomery, 1973) and cyclododecane (Atavin et al, 1989). For solution and solid state samples NMR spectroscopy have provided valuable information for temperature-dependent conformational analysis as given for cyclononane (Anet & Krane, 1980), cyclodecane (Pawar et al, 1998), cycloundecane (Brown, Pawar & Noe, 2003), and cyclododecane (Anet & Rawdah, 1978). In all these experimental investigation a population conformation with an uncertainty of ±5% was reported, and so the preferred conformation for each cycloalkane containing 7 to 12 carbon atoms precisely determined.…”
Section: Conformational Analysis Of Cycloalkanesmentioning
confidence: 99%
“…The structures of the lower-energy conformations have been studied via electron diffraction (Hilderbrandt, Wieser & Montgomery, 1973), X-ray crystallography (Shenhav & Schaeffer, 1981) and dynamic NMR spectroscopy (Pawar et al, 1998). The boat-chair-boat (BCB) conformation for the cyclodecane has been found in the solid state by X-ray diffraction (Shenhav & Schaeffer, 1981) near 173 K and assigned as the most stable form.…”
Section: Cyclodecanementioning
confidence: 99%
See 2 more Smart Citations